Understanding the Value of Data Ecosystems for Circular Economy Metrics - Pottebaum, Jens; Dietrich, Katrin; Schmidt, Lara; Biglari, Mostafa; Schmidt, Michael-Georg; Pistillo, Alessandro; Gravina, Nadja; Schmidt, Franziska
The Circular Economy is considered a key approach to addressing resource scarcity, rising raw material prices, and the need for more resilient value chains. However, its practical implementation is often hindered by the lack of suitable and standardized metrics, as well as by high requirements for horizontal and vertical data integration. This white paper illustrates, through selected Manufacturing-X projects, how federated data ecosystems can help establish Circular Economy metrics as an effective management instrument for growth, margin protection, and resilience. Based on literature, industrial practice, and demonstrators, Circular Economy metrics are structured into four groups: overarching assessment approaches, disassembly-related indicators, lifetime-oriented metrics, and end-of-life and recycling-focused indicators. Use cases from Construct-X, Decide4ECO, Fluid 4.0, Chem-X, and other Manufacturing-X initiatives demonstrate the benefits of data-driven approaches for product, component, and material loops. At the same time, they reveal a current lack of interoperable, cross-industry standards for both metrics and data models. The white paper concludes that data ecosystems such as Manufacturing-X are a key enabler for scaling circular business models. In particular, shared cross-sector frameworks for metrics, standardized information models based for example on the Asset Administration Shell, and the integration of circular metrics into existing systems and processes are essential. The work presented therefore marks an important step toward a data-driven and economically viable Circular Economy.
Keywords: Circular Economy; Circular Economy Metrics; Manufacturing-X; Data Ecosystems

Correlation between interlaminar shear strength of CFRP and joint strength of aluminium-CFRP hybrid joints - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
Fibre-reinforced polymers are increasingly used due to their high specific strength, making them suitable for local sheet metal reinforcement. This allows improved overall mechanical properties with reduced wall thickness of the sheet metal part and, thus, lower weight of the components. One of the main focuses of research into such hybrid structures is on the adhesive properties and the respective failure behaviour of the interfaces. Generally, the failure behaviour under the influence of mechanical loads can be divided into adhesive, cohesive and mixed-mode failure. The correlation between observed failure behaviour and adhesion properties of the hybrid composite materials is analysed in detail in this work. The hybrid composite consists of an aluminium sheet of the alloy EN AW‑6082 T6 and thermoset carbon fibre-reinforced plastic (CFRP) prepreg. The aluminium sheet was laser pretreated before hybrid production to improve the adhesion properties. The specimens studied were produced by the prepreg pressing process, in which the components are cured and joined simultaneously. The influences of the thickness of the CFRP part, the layup, the fibre orientation at the boundary layer, and the laser pretreatment parameters on the properties of the hybrid joints were investigated.
Keywords: Prepreg pressing process; hybrid joints; laser surface pretreatment; intrinsic manufacturing; CFRP; aluminium; materials engineering

In Situ Alloying of Ti-6Al-7Nb with Copper Using Laser Powder Bed Fusion - Steinmeier, Paul; Hoyer, Kay-Peter; Lopes Dias, Nelson Filipe; Zielke, Reiner; Tillmann, Wolfgang; Schaper, Mirko (Crystals)
Titanium alloys are widely employed for biomedical implants due to their high strength, biocompatibility, and corrosion resistance, yet their lack of intrinsic antibacterial activity remains a major limitation. Incorporating copper, an antibacterial and β-stabilising element, offers a promising strategy to enhance implant performance. This study investigates Ti-6Al-7Nb modified with 1–9 wt.% Cu via in situ alloying during metal-based laser powder bed fusion (PBF-LB/M), with the aim of assessing processability, microstructural evolution, and mechanical properties. Highly dense samples (>99.9%) were produced across all Cu levels, though chemical homogeneity strongly depended on processing parameters. Increasing Cu content promoted β-phase stabilisation, Ti2Cu precipitation, and pronounced grain refinement. Hardness and yield strength increased nearly linearly with Cu addition, while ductility decreased sharply at ≥5 wt.% Cu due to intermetallic formation, hot cracking, and brittle fracture. These results illustrate both the opportunities and constraints of rapid alloy screening via PBF-LB/M. Overall, moderate Cu additions of 1–3 wt.% provide the most favourable balance between mechanical performance, manufacturability, and potential antibacterial functionality. These findings provide a clear guideline for the design of Cu-functionalised titanium implants and demonstrate the efficiency of in situ alloy screening for accelerated materials development.
Keywords: Biomaterial; In Situ Alloying; Titanium; Additive Manufacturing

Single-step self-punching lockbolt process for aluminum sheets without pre-hole - Han, Daxin; Kappe, Fabian; Vorderbrüggen, Julian; Jendrny, Jörg; Gorr, Eugen; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Dynamics of an Absorption/Desorption Plant: Experimental Study and Model Validation - Weber, Mike; Lutters, Nicole; Kenig, Eugeny Y. (Industrial & Engineering Chemistry Research)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

Data-driven simulation-based decision support system for resource allocation in industry 4.0 and smart manufacturing - Mahmoodi, Ehsan; Fathi, Masood; Tavana, Madjid; Ghobakhloo, Morteza; Ng, Amos H.C. (Journal of Manufacturing Systems)
Keywords: Industrial and Manufacturing Engineering; Hardware and Architecture; Software; Control and Systems Engineering

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (17th CIRP Conference on Intelligent Computation in Manufacturing Engineering)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Effect of Substrate Temperature on Bead Track Geometry of 316L in Directed Energy Deposition: Investigation and Regression Modeling - Chalicheemalapalli Jayasankar, Deviprasad; Gnaase, Stefan; Lehnert, Dennis; Walter, Artur; Rohling, Robin; Tröster, Thomas (Metals)
The optimization of process parameters in powder Directed Energy Deposition (DED) is essential for achieving consistent, high-quality bead geometries, which directly influence the performance and structural integrity of fabricated components. As a subset of additive manufacturing (AM), the DED process, also referred to as laser metal deposition (LMD), enables precise, layer-by-layer material deposition, making it highly suitable for complex geometries and part repair applications. Critical parameters, such as the laser power, feed rate, powder mass flow, and substrate temperature govern the deposition process, impacting the bead height, width, contact angle, and dilution. Inconsistent control over these variables can lead to defects, such as poor bonding, dimensional inaccuracies, and material weaknesses, ultimately compromising the final product. This paper investigates the effects of various process parameters, specifically the substrate temperature, on bead track geometry in DED processes for stainless steel (1.4404). A specialized experimental setup, integrated within a DED machine, facilitates the controlled thermal conditioning of sample sheets. Using Design of Experiments (DoE) methods, individual bead marks are generated and analyzed to assess geometric characteristics. Regression models, including both linear and quadratic approaches, are constructed to predict machine parameters for achieving the desired bead geometry at different substrate temperatures. Validation experiments confirm the accuracy and reliability of the models, particularly in predicting the bead height, bead width, and contact angle across a broad range of substrate temperatures. However, the models demonstrated limitations in accurately predicting dilution, indicating the need for further refinement. Despite some deviations in measured values, successful fabrication is achieved, demonstrating robust bonding between the bead and substrate. The developed models offer insights into optimizing DED process parameters to achieve desired bead characteristics, advancing the precision and reliability of additive manufacturing technology. Future work will focus on refining the regression models to improve predictions, particularly for dilution, and further investigate non-linear interactions between process variables.
Keywords: additive manufacturing; direct energy deposition; laser metal deposition

Advancements in Hybrid Additive Manufacturing: Integrating SLM and LMD for High-Performance Applications - Chalicheemalapalli Jayasankar, Deviprasad; Gnaase, Stefan; Kaiser, Maximilian Alexander; Lehnert, Dennis; Tröster, Thomas (Metals)
Additive manufacturing (AM) technologies enable near-net-shape designs and demand-oriented material usage, which significantly minimizes waste. This points to a substantial opportunity for further optimization in material savings and process design. The current study delves into the advancement of sustainable manufacturing practices in the automotive industry, emphasizing the crucial role of lightweight construction concepts and AM technologies in enhancing resource efficiency and reducing greenhouse gas emissions. By exploring the integration of novel AM techniques such as selective laser melting (SLM) and laser metal deposition (LMD), the study aims to overcome existing limitations like slow build-up rates and limited component resolution. The study’s core objective revolves around the development and validation of a continuous process chain that synergizes different AM routes. In the current study, the continuous process chain for DMG MORI Lasertec 65 3D’s LMD system and the DMG MORI Lasertec 30 3D’s was demonstrated using 316L and 1.2709 steel materials. This integrated approach is designed to significantly curtail process times and minimize component costs, thus suggesting an industry-oriented process chain for future manufacturing paradigms. Additionally, the research investigates the production and material behavior of components under varying manufacturing processes, material combinations, and boundary layer materials. The culmination of this study is the validation of the proposed process route through a technology demonstrator, assessing its scalability and setting a benchmark for resource-efficient manufacturing in the automotive sector.
Keywords: additive manufacturing (AM); selective laser melting (SLM); laser metal deposition (LMD); hybrid manufacturing; process optimization; 316L; 1.2709

Pseudo-Labeling Machine Learning Algorithm for Predictive Maintenance of Relays - Winkel, Fabian; Wallscheid, Oliver; Scholz, Peter; Böcker, Joachim (IEEE Open Journal of the Industrial Electronics Society)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Control and Systems Engineering

Softsensors: key component of property control in forming technology - Homberg, Werner; Arian, Bahman; Arne, Viktor; Borgert, Thomas; Brosius, Alexander; Groche, Peter; Hartmann, Christoph; Kersting, Lukas; Laue, Robert; Martschin, Juri; Meurer, Thomas; Spies, Daniel; et al. (Production Engineering)
Abstract The constantly increasing challenges of production technology for the economic and resource-saving production of metallic workpieces require, among other things, the optimisation of existing processes. Forming technology, which is confronted with new challenges regarding the quality of the workpieces, must also organise the individual processes more efficiently and at the same time more reliably in order to be able to guarantee good workpiece quality and at the same time to be able to produce economically. One way to meet these challenges is to carry out the forming processes in closed-loop control systems using softsensors. Despite the many potential applications of softsensors in the field of forming technology, there is still no definition of the term softsensor. This publication therefore proposes a definition of the softsensor based on the definition of a sensor and the distinction from the observer, which on the one hand is intended to stimulate scientific discourse and on the other hand is also intended to form the basis for further scientific work. Based on this definition, a wide variety of highly topical application examples of various softsensors in the field of forming technology are given.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Editorial: Remote @ Distance - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Coworking - Krause, Ina (Arbeit)
Zusammenfassung Der Beitrag beschäftigt sich mit dem Konzept Coworking und arbeitet auf Basis eigener empirischer Daten heraus, wie dieses Konzept im Zuge seiner wachsenden Verbreitung und der Etablierung von Coworking-Spaces als ‚dritten Orten der Arbeit‘ Legitimität für neue Gestaltungsideen und Wertvorstellungen von Büroarbeit generiert. Coworking-Spaces werden dabei als ‚dritte Orte‘ definiert, die dem Raumkonzept der Schaffung einer flexibel anpassbaren und Kreativität fördernden Arbeitsumgebung für Büroarbeiter:innen folgen. Das Geschäftskonzept Coworking-Space wird inzwischen aber auch als alternatives Organisationsmodell von Arbeit wahrgenommen. Dem Beitrag liegt das Forschungsinteresse zugrunde zu erkunden, wie und in welchen Variationen das Konzept Coworking in Büroarbeitsorganisationen, die sich selbst als Coworking-Space bezeichnen, adaptiert und praktisch umgesetzt wird. Nachgezeichnet wird, inwiefern Coworking als alternatives Gestaltungsmodell oder, im Sinne von Meyer und Rowan, Rationalisierungskonzept der Organisation von Arbeit Elemente eines neuen Normalitätsverständnisses von Büroarbeit generiert, welches über Betreiber:innen von Coworking-Spaces und Coworker:innen inzwischen in die Breite der Arbeitsgesellschaft getragen wird.
Keywords: Industrial and Manufacturing Engineering

Frontmatter - Krause, Ina; Jacobsen, Heike; Gerhards, Christian (Arbeit)
Keywords: Industrial and Manufacturing Engineering

Online load balancing on uniform machines with limited migration - Maack, Marten (Operations Research Letters)
Keywords: Applied Mathematics; Industrial and Manufacturing Engineering; Management Science and Operations Research; Software

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites